Radioprotective Agents Based on Complex Compounds of 3d Metals with Vitamins and Aminoacids - N. M. Kebets; A. P. Kebets; G. A. Prigorelov (Вестник войск РХБ защиты, 2025)
Complex compounds of iron(II) and cobalt(II) that contain vitamins С, В2, and В5 have radioprotective potential and are atoxic.Such compounds can be used as radioprotective agents in case of nuclear explosion threat, before people step out onto surface that has been contaminated with nuclear explosion products or during nuclear accident settlement.Relevance. Many existing radioprotective agents reveal unwanted side effects, when used. They are also sometimes unavailable. The development of new chemical compounds that exert radioprotective effect provides new possibilities for radioprotection of troops and population of the Russian Federation.Purpose of the study. The purpose of the study is to analyze radioprotective effect of complex compounds of iron(II) and cobalt(II) that contain vitamins С, В2, and В5 in case of acute radiation damage.Materials and methods. The experimental studies radioprotective properties of complex compounds of iron(II) and cobalt(II) in case of acute radiation damage have been conducted. The tests have been performed on laboratory mice. The mice have been exposed to radiation fractionally in 3 stages. The interval between them is 30 days and the radiation doses are 5.4, 3.0, and 6.5 Gr, respectively. The authors have taken into account the radiation exposure equability and dose accuracy. The evaluation of radioprotective efficiency of agents is based on the comparative analysis of changes in indicator values of redistributive shifts in blood samples, signs of direct radiation damage of lymphoid and blood forming tissues and the reactions of vascular and nervous systems to such damages, as well as the outcomes of acute radiation syndrome in control and test groups of mice at three stages of the experiment.Results. Survival rate in mice, who have been treated with a complex iron compound, is 100%, while survival rate in mice, who have been treated with a cobalt compound is 80%, and the survival rate in mice, who have been treated with Vetoron E is only 40%.Conclusion. Complex compounds of iron and cobalt that contain vitamins С, В2, and В5 exhibit radioprotective properties. They enhance the resistance to ionizing emission and don’t exert toxic impact on the organism of a living being.